EFETIVIDADE DA REVISÃO EM UM ÚNICO TEMPO PARA TRATAMENTO DAS INFECÇÕES PERIPROTÉTICAS - Unfried, Ricardo Issler (2019)
Prosthetic joint infection is a devastating complication that can affect hip arthroplasty. Its treatment is extremely difficult and issues regarding the optimal treatment remain unanswered. This study intended to show the effectiveness of one stage treatment of periprosthetic infections. A retrospective observational cohort study was performed from November 2013 to August 2017. Eighteen patients with suspected periprosthetic infection were included. To define infection, the major and minor criteria developed by the International Consensus Group on Periprosthetic Joint Infection. Laboratory tests were performed and all patients were followed for at least one year. The mean age was 69,83±9,76 years. Fourteen patients (94.5%), out of 15, were free of infection in the two years of follow- up. Three (16.7%) patients have not yet completed the two-year follow-up, but they do not have any complaints, signs or symptoms that show the relapse of the infection. Of the patients in whom bone graft was used, all presented no signs of relapse of infection in the two-year follow-up period. The treatment through one stage revision surgery is a viable option with acceptable results even when the reconstruction is necessary through the use of a bone graft. Elevated healing rates can be achieved with the use of this surgical method.